The Impact of Workload, Work Stress and Work Environment on Nurse Performance at QADR Hospital, Tangerang Regency - Rusdiana, Endang; Istiqomah; Nurdin, Abidin Candra; Hermawan, Rangga Adhitia (Lafadz Jaya Publisher, 2025)
Human resources are an important component in efforts to achieve planned company goals. Human resource development efforts of each company are very important to realize human resource development in various aspects. Discussion of performance is often carried out by Human Resources researchers, because performance has an important role in the improvement and work system of each company. saturated sampling or total sampling is a sampling technique in which all members of the population are sampled. This technique is often used when the population is relatively small or when researchers want to make generalizations with very small errors. So the sample used in this study was 116 nurses at QADR Hospital, Tangerang Regency. the results of the study found that workload, work stress and work environment affect performance by 38.8%. the results of the study showed that of the three independent variables proposed in the study, only the workload variable had a partial effect on performance. this shows that the lower the workload received by an employee, the performance will increase.